Direct Selling: The Role of Risk In Consumer’s Acceptance and Satisfaction - Alturas, Bráulio (2004)
This paper considers the role of perceived risk in consumer’s satisfaction and acceptance of direct selling. Direct selling has been exhibiting in the last decade substantial growth in sales revenues and number of salespeople involved. Also the acceptance on the part of the consumers has been increasing; in spite of they show more and more demanding and informed. The literature reveals that the relationship between customer satisfaction and direct selling has not been sufficiently studied, yet. This paper, applying a quantitative approach attempts to provide some data on this relation. Results indicate that there is a negative correlation between perceived risk and direct selling acceptance and also a positive correlation between direct selling acceptance and satisfaction.